South Pacific paradise rewritten - Lovensheimer, Jim (Broadway legacies, 2010)
This book explores the show's complex messages and demonstrates how the presentation of those messages changed throughout the creative process. Jim Lovensheimer shows how Rodgers and especially Hammerstein continually refined and softened the theme of racial intolerance until it was more acceptable to mainstream Broadway audiences. -- [book jacket].